Genus- and family-group names in the order Embioptera (Insecta) - Miller, Kelly B. (Zootaxa, 2009)
All available genusand family-group names in the Embioptera (Embiidina, Embiodea) are listed along with the original citation, original and current status, and the type taxon and method of designation. The early literature is reviewed, and the following taxonomic acts are established: 1) Embia brasiliensis Gray in Griffith and Pidgeon 1832 is fixed as the type species of Olyntha Gray in Griffith and Pidgeon 1832 (junior homonym, replaced by Embolyntha Davis) using the First Revisor Principle, 2) Embia savignii Westwood 1837 is fixed as type species of Euembia Verhoeff 1904, and 3) Saussurembia davisi Ross 1992 is synonomized with Saussurembia ruficollis Davis 1939. Numerous other taxonomic problems are examined and clarified and the various ordinal names briefly summarized.